2010
DOI: 10.1038/hdy.2010.129
|View full text |Cite
|
Sign up to set email alerts
|

A 6-bp deletion in the TYRP1 gene causes the brown colouration phenotype in Chinese indigenous pigs

Abstract: Brown coat colour has been described in Chinese-Tibetan, Kele, and Dahe pigs. Here, we report the identification of a causal mutation underlying the brown colouration. We performed a genome-wide association study (GWAS) on Tibetan and Kele pigs, and found that brown colours in Chinese breeds are controlled by a single locus on pig chromosome 1. By using a haplotype-sharing analysis, we refined the critical region to a 1.5-Mb interval that encompasses only one pigmentation gene: tyrosinaserelated protein 1 (TYR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 30 publications
0
43
0
3
Order By: Relevance
“…Mutations in TYRP1 , which is highly conserved in vertebrates, have been shown to lighten skin and/or hair pigmentation in several species including pigs, dogs, mice and zebra fish (Fig. 3A; 15, 1619). In humans, previously discovered rare mutations leading to complete loss of function for TYRP1 are known to cause OCA3 or rufous albinism (20, 21).…”
mentioning
confidence: 99%
“…Mutations in TYRP1 , which is highly conserved in vertebrates, have been shown to lighten skin and/or hair pigmentation in several species including pigs, dogs, mice and zebra fish (Fig. 3A; 15, 1619). In humans, previously discovered rare mutations leading to complete loss of function for TYRP1 are known to cause OCA3 or rufous albinism (20, 21).…”
mentioning
confidence: 99%
“…Also, the duplication of the Kit gene is associated dominant white mutation pigs [10]. In addition, the molecular events of variable pig genes shown that different coat colors such as missense mutation of melanocortin 1 recpetor (MC1R) [24], copy number variation and splice mutation of Kit [25], 6 bp deletion of tyrosinase related protein1 (TRYP1) [26], missense 176 mutation of endothelin receptor beta (EDNRB) [27,28], missense mutations of Kit ligand (KITLG) [29], and missense mutations of oculocutaneous albinism 2 (OCA2) [30].…”
Section: Discussionmentioning
confidence: 99%
“…A cor da pelagem é uma das características mais marcantes nos mamíferos, é também uma das características que apresenta grande diversidade entre as espécies, bem como dentro de espécie (Ren et al, 2011 …”
Section: Controle Genético Dos Mecanismos De Pigmentaçãounclassified
“…A cor da pelagem é uma das características mais marcantes nos mamíferos, é também uma das características que apresenta grande diversidade entre as espécies, bem como dentro de espécie (Ren et al, 2011 Os melanócitos produzem dois tipos de melaninas, as eumelaninas, substâncias químicas responsáveis pelos pigmentos negro e castanho e as feomelaninas pelos os pigmentos vermelho e amarelo (Gratten et al, 2010). Contudo, o processo de determinação da coloração de pele, pelos e olhos tem início durante o desenvolvimento embrionário, quando os melanócitos formados na crista neural migram por todo o corpo do feto, até alcançarem os lugares que lhe são determinados no corpo, para isso é necessário um programa de regulação muito eficiente para garantir que as quantidades de células necessárias cheguem aos seus locais determinados.…”
Section: Controle Genético Dos Mecanismos De Pigmentaçãounclassified
See 1 more Smart Citation